A displacement-based design method for medium-rise reinforced concrete walls (2010)
In displacement-based design methods some demand considerations, starting from the first mode of vibration, are usually made. However, some authors have called the attention on the importance of taking the higher modes into account, due to their influence in the distribution and demand of both, moments and shears along the vertical elements, with significant effects. In this work, the method presented allows to consider, in a practical way, the effect of the higher modes on the seismic response of a structure. The proposal to achieve it, is a simplified model of Three Degree of-Fredom developed from a mass concentration of four points equally distant along the building height. This method corresponds to an iterative process, in which the analysis and design procedures are carried out simultaneously, thus, avoiding considerations or suppositions on resistance and ductility values. This method has been applied to the structural walls of a 15-storey building. The results obtained show the efficiency of the method in terms of the proposed objectives achievement and the fast converging of the iterative process involved. The effect of the higher modes is extremely noticeable in the distribution of shear stresses and the use of an initial pre-dimensioning involving the reinforcement, allows consistency between the analysis and the structural design.